Combination Treatment With Antihypertensive Agents Enhances the Effect of Qiliqiangxin on Chronic Pressure Overload–induced Cardiac Hypertrophy and Remodeling in Male Mice. Issue 6 (June 2015) - Ye, Yong; Gong, Hui; Wang, Xingxu; Wu, Jian; Wang, Shijun; Yuan, Jie; Yin, Peipei; Jiang, Guoliang; Li, Yang; Ding, Zhiwen; Zhang, Weijing; Zhou, Jingmin; et al.
Abstract : Abstract: We previously showed that Qiliqiangxin (QL) capsules could ameliorate cardiac hypertrophy and remodeling in a mouse model of pressure overload. Here, we compared the effects of QL alone with those of QL combined with the following 3 types of antihypertensive drugs on cardiac remodeling and dysfunction induced by pressure overload for 4 weeks in mice: an angiotensin II type 1 receptor (AT1 -R) blocker (ARB), an angiotensin-converting enzyme inhibitor (ACEI), and a β-adrenergic receptor (β-AR) blocker (BB). Adult male mice (C57B/L6) were subjected to either transverse aortic constriction or sham operation for 4 weeks, and the drugs (or saline) were orally administered through gastric tubes. Cardiac function and remodeling were evaluated through echocardiography, catheterization, histology, and analysis of hypertrophic gene expression. Cardiomyocyte apoptosis and autophagy, AT1 -R and β1 -AR expression, and cell proliferation–related molecules were also examined. Although pressure overload–induced cardiac remodeling and dysfunction, hypertrophic gene reprogramming, AT1 -R and β1 -AR expression, and ERK phosphorylation were significantly attenuated by QL alone, QL + ARB, QL + ACEI, and QL + BB, the attenuation was stronger in the combination treatment groups. Moreover, apoptosis was reduced to a larger extent by each combination treatment than by QL alone, whereas autophagy was more strongly attenuated by either QL + ARB or QL + ACEI. None of the treatments significantly upregulated ErbB2 or ErbB4 phosphorylation, and none significantly downregulated C/EBPβ expression. Therefore, the effects of QL on chronic pressure overload–induced cardiac remodeling may be significantly increased when QL is combined with an ARB, an ACEI, or a BB. Abstract : Supplemental Digital Content is Available in the Text.